A novel method to purify small RNAs from human tissues for methylation analysis by LC-MS/MS - Yang, Rong; Li, Jianfeng; Wu, Yifan; Jiang, Xinli; Qu, Shuang; Wang, Qiang; Liang, Hongwei; Zen, Ke (Frontiers in Molecular Biosciences, 2022)
Methylation modification of small RNAs, including miRNA, piRNA, and tsRNA, is critical for small RNA biogenesis and biological function. Methylation of individual small RNA can be defined by liquid chromatography-coupled with mass spectrometry (LC-MS/MS). However, LC-MS/MS analysis requires a high purity of individual small RNA. Due to the difficulty of purifying specific small RNA from tissues or cells, the progress in characterizing small RNA methylation by LC-MS/MS is limited. Here, we report a novel method that can efficiently purify small RNA from human tissues for LC-MS/MS analysis. This method includes two steps: 1) pull down the target small RNA by incubating total small RNAs (18–24 nt) extracted from human tissues with a biotinylated antisense oligonucleotide of the target small RNA, followed by capturing the binding duplex of biotinylated antisense and small RNA via streptavidin magnetic beads, and 2) protect the target small RNA by pairing it with a single-strand DNA, which sequence is complementary to the target small RNA, to form a DNA/RNA hybrid double-strand, followed by sequential digestion with exonuclease I, nuclease S1, and DNase I, respectively. Furthermore, employing a mixture of four pairs of synthetic methylated and non-methylated small RNAs, we further refined this two-step method by optimizing the nuclease S1 treatment condition. With this method, we successfully purified miR-21-5p, miR-26-5p, piR-020485, and tsRNA from human lung and sperm tissue samples and analyzed their 2′-O-methylation modification at the 3′-end by LC-MS/MS.